2011
DOI: 10.1136/amiajnl-2011-000308
|View full text |Cite
|
Sign up to set email alerts
|

Health information exchange usage in emergency departments and clinics: the who, what, and why

Abstract: HIE use in emergency departments and ambulatory clinics was focused on patients where missing information was believed to be present in the exchange and was related to factors including the roles of people with access, the setting, and other site-specific issues that impacted the overall breadth of routine system use. These data should form an important foundation as other sites embark upon HIE implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
100
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 18 publications
(3 reference statements)
13
100
0
Order By: Relevance
“…In our study, physicians reported workflow challenges due to several factors that have caused disruptions to their workflow such as a slow system response time and multiple logins. Single sign-on or more contextaware system integration are necessary to increase usage of the RHIOs' web-based portals, especially for physicians [20,54]. Interestingly, our interviews also indicated that the more information presented to the users may not always be better.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our study, physicians reported workflow challenges due to several factors that have caused disruptions to their workflow such as a slow system response time and multiple logins. Single sign-on or more contextaware system integration are necessary to increase usage of the RHIOs' web-based portals, especially for physicians [20,54]. Interestingly, our interviews also indicated that the more information presented to the users may not always be better.…”
Section: Discussionmentioning
confidence: 87%
“…Addressing these problem first would help minimize the challenges associated with the poor availability of information in the system and users low levels of search confidence. Such problems often leads to reduced usage of HIE [20]. We propose the following recommendations as to how these challenges can be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The results, if supported by additional research, can drive IT implementation and use at EDs in spite of barriers and challenges reported in the literature (Menachemi, Brooks, Schwalenstocker, & Simpson, 2009). It also hints at potential positive outcomes of using such a system that can be quantified, as opposed to other studies that yielded mixed results concerning benefits of using healthcare IT in general, and EMRs in particular (Furukawa, 2011;Gagnon et al, 2012;Johnson et al, 2011;Kellermann & Jones, 2013). It will thus be quite straightforward to calculate the ROI of such systems if field evaluations of the system yield similar results.…”
Section: Expected Contributionmentioning
confidence: 67%
“…As can be seen, the total time is split almost evenly between reduce and the cryptographic operations for data at level 3 and is dominated by reduce for data at level 2. Johnson et al [18] report approximately 81 accesses per day in a typical HIE. Based on this number, we calculate the total time for auditing all accesses in a day and in a month to be 6.57/5.41 seconds (level 3/level 2) and 3.26/2.68 minutes, respectively.…”
Section: Implementation and Evaluationmentioning
confidence: 99%
“…(ms) [18]). The external audit data has a size of 12 MB, and includes roughly 9,644 entries about patient registration, billing and referral.…”
Section: Implementation and Evaluationmentioning
confidence: 99%